2020
DOI: 10.14202/vetworld.2020.1182-1186
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lower urinary tract disease in the Yogyakarta cat population, Indonesia

Abstract: Background and Aim: This paper reports a retrospective study performed in 185 cats diagnosed with feline lower urinary tract disease (FLUTD). The analyzed population involved feline patients at the Veterinary Clinic of Universitas Gadjah Mada, Indonesia. This research aimed to evaluate the clinical indications and causes of FLUTD in the Yogyakarta cat population. Materials and Methods: The medical data of all feline patients were obtained to conduct this study. FLUTD diagnoses were based on physical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 20 publications
4
15
0
1
Order By: Relevance
“…These findings, combined with some results mentioned in Sparkes's review and some unpublished data ( 22 ), confirm that FLUTD occurs commonly, accounting for ~1.5–4.5% of the whole feline caseload in veterinary clinics. The prevalence of cats classified as FIC in FLUTD cats was reported to be 55% in 1991 ( 23 ), and 63% in 2001 in the United States ( 5 ), and has been estimated to be 57% in Switzerland ( 8 ), 55% in Germany ( 24 ), 55.5% in Norway ( 11 ), 60.7% in Poland ( 25 ), 66.4% in Korea ( 20 ), 57.7% in Thailand ( 21 ), and 56% in Indonesia ( 26 ). Therefore, it can be concluded that the prevalence of FIC among cats with FLUTD ranged from 55% to around 67% and FIC is the most frequent cause of FLUTD ( Figure 1 ).…”
Section: Epidemiologymentioning
confidence: 99%
“…These findings, combined with some results mentioned in Sparkes's review and some unpublished data ( 22 ), confirm that FLUTD occurs commonly, accounting for ~1.5–4.5% of the whole feline caseload in veterinary clinics. The prevalence of cats classified as FIC in FLUTD cats was reported to be 55% in 1991 ( 23 ), and 63% in 2001 in the United States ( 5 ), and has been estimated to be 57% in Switzerland ( 8 ), 55% in Germany ( 24 ), 55.5% in Norway ( 11 ), 60.7% in Poland ( 25 ), 66.4% in Korea ( 20 ), 57.7% in Thailand ( 21 ), and 56% in Indonesia ( 26 ). Therefore, it can be concluded that the prevalence of FIC among cats with FLUTD ranged from 55% to around 67% and FIC is the most frequent cause of FLUTD ( Figure 1 ).…”
Section: Epidemiologymentioning
confidence: 99%
“…Feline lower urinary tract disease (FLUTD) is a common feline disease characterized by urinary bladder and urethral dysfunction [1,2]. FLUTD is a broad term for many disorders, including feline idiopathic cystitis (FIC), urethral plaque (UP), urolithiasis, urinary tract neoplasia and urinary tract infection (UTI) [1]. Common clinical manifestations of the disease include dysuria, haematuria, stranguria, pollakiuria and periuria [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…A review of the relevant literature indicated that FIC was the most frequently diagnosed disease (55%-60%) among lower urinary tract diseases [1][2][3][4][5][6][7]. Urethral obstruction is a prevalent complication of the disease, especially in male cats [3,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kasus FLUTD sering kali dapat dikenali ketika kucing menunjukkan gejala klinis antara lain hematuria, pollakiuria, stranguria, periuria, disuria dan membesarnya VU (Dorsch et al, 2014;Lund et al 2015;Nururrozi et al, 2020). Pada tahap awal gejala klinis tersebut sering kali tidak dikenali oleh pemiliknya, sehingga gangguan akan menjadi lebih parah.…”
unclassified